2013
DOI: 10.1371/journal.pone.0068376
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr Modulates Macrophage Metabolic Pathways: A SILAC-Based Quantitative Analysis

Abstract: Human immunodeficiency virus type 1 encoded viral protein Vpr is essential for infection of macrophages by HIV-1. Furthermore, these macrophages are resistant to cell death and are viral reservoir. However, the impact of Vpr on the macrophage proteome is yet to be comprehended. The goal of the present study was to use a stable-isotope labeling by amino acids in cell culture (SILAC) coupled with mass spectrometry-based proteomics approach to characterize the Vpr response in macrophages. Cultured human monocytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 67 publications
4
93
0
Order By: Relevance
“…3,13 Our earlier studies using SILAC-based proteomics analysis demonstrated that numerous enzymes in the glycolytic pathway and TCA cycle were altered in response to HIV-1 Vpr in macrophages. 16 In this study, we evaluated alteration in metabolic profile in response to HIV-1 Vpr in macrophages to correlate with the observed changes in expression profile of critical enzymes in the glycolytic pathway and TCA cycle. In fact, metabolomics has provided sensitive, fast, and robust tools for analyzing metabolite levels during viral infections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,13 Our earlier studies using SILAC-based proteomics analysis demonstrated that numerous enzymes in the glycolytic pathway and TCA cycle were altered in response to HIV-1 Vpr in macrophages. 16 In this study, we evaluated alteration in metabolic profile in response to HIV-1 Vpr in macrophages to correlate with the observed changes in expression profile of critical enzymes in the glycolytic pathway and TCA cycle. In fact, metabolomics has provided sensitive, fast, and robust tools for analyzing metabolite levels during viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…16 To corroborate changes in the intracellular and extracellular metabolite levels we assessed the expression levels of selected enzymes in the TCA cycle in response to HIV-1 Vpr overexpression in U937 macrophages in comparison to the control Ad-null transduced macrophages on day 1, 3 and 7 (Fig. 4).…”
Section: Vpr In Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…ATP5B was shown to be upregulated by Tat protein of HIV-1 virus (López-Huertas et al, 2013). ATP5B protein was also shown to be physically interacted with Vpr, a HIV-1 virus protein in HEK293 cells (Barrero et al, 2013). Metabolic changes are common characteristic features of cancer tissues.…”
Section: Functionmentioning
confidence: 99%